Loss function of NtGA3ox1 delays flowering through impairing gibberellins metabolite synthesis in Nicotiana tabacum - Deng, Lele; Li, Chaofan; Gao, Qian; Yang, Wenwu; Jiang, Jiarui; Xing, Jiaxin; Xiang, Haiying; Zhao, Jun; Yang, Yekun; Leng, Pengfei (Frontiers in Plant Science, 2023)
Flowering time, plays a crucial role in tobacco ecological adaptation besides its substantial influence on tobacco production and leaf quality. Meanwhile, it is sensitive to biotic or abiotic challenges. The plant hormones Gibberellins (GAs), controlling a number of metabolic processes, govern plants growth and development. In this study, we created a late flowering mutant HG14 through knocking out NtGA3ox1 by CRISPR/Cas9. It took around 13.0 and 12.1 days longer to budding and flowering compared to wild type Honghuadajinyuan. Nearly all of the evaluated agronomic characters deteriorated in HG14,showing slower growth and noticeably shorter and narrower leaves. We found that NtGA3ox was more prevalent in flowers through quantitative reverse transcription PCR analysis.Transcriptome profiling detected 4449, 2147, and 4567 differently expressed genes at the budding, flowering, and mature stages, respectively. The KEGG pathway enrichment analysis identified the plant-pathogen interaction, plant hormone signal transduction pathway, and MAPK signaling pathway are the major clusters controlled by NtGA3ox1 throughout the budding and flowering stages. Together with the abovementioned signaling pathway, biosynthesis of monobactam, metabolism of carbon, pentose, starch, and sucrose were enriched at the mature stage. Interestingly, 108 up-and 73 down-regulated DEGs, impairing sugar metabolism, diterpenoid biosynthesis, linoleic and alpha-linolenic acid metabolism pathway, were continuously detected accompanied with the development of HG14. This was further evidenced by the decreasing content of GA metabolites such as GA4 and GA7, routine chemicals, alkaloids, amino acids, and organic acids Therefore, we discovered a novel tobacco flowering time gene NtGA3ox1 and resolved its regulatory network, which will be beneficial to the improvement of tobacco varieties.